The representation of coupling interactions in the Material Properties Open Database (MPOD). (17th November 2017) - Fuentes-Cobas, Luis E.; Chateigner, Daniel; Fuentes-Montero, María E.; Pepponi, Giancarlo; Grazulis, Saulius
ABSTRACT: The Material Properties Open Database (MPOD, http://mpod.cimav.edu.mx ) is a functional element of the web-based open databases system linked with crystallography. MPOD delivers single-crystal tensor properties in several representations, ranging from numerical matrices to 3D printing. Longitudinal moduli surfaces can be displayed in computers as well as in smart cell phones. Properties are stored as '.mpod' files. IUCr formatting standards (CIF) are followed. The original published paper containing the data is cited. Structural and experimental information is also registered and linked. 'Coupling properties', say piezo-effects and magnetoelectricity, represent interactions linking different subsystems in a material. Currently, piezoelectricity occupies a significant fraction of cases in MPOD. The implications of crystal symmetry in piezoelectricity are systematically taken into account. Matrices' elements and longitudinal moduli surfaces are checked for consistency with the Neumann principle. The inclusion of magnetoelectric axial tensors introduces exciting features into MPOD.